The risk of sleep-related death in an inclined sleep environment - Laura R. Sangaré; Lance Kaufman; Robert A. Bardwell; Deborah Nichols; Mersine Bryan (BMC, 2024)
Abstract Background Unsafe sleep environments are the primary modifiable risk factor for sudden unexpected infant death (SUID). Despite this knowledge, products that deviate from the American Academy of Pediatrics (AAP) safe sleep recommendations continue to be commonplace, such as inclined sleepers. Analyses to estimate risk among these products are lacking, perpetuating their presence in the marketplace. We present a method of comparing risk of SUID in an inclined sleeper to an AAP-recommended sleep environment. Methods A case-control analysis using publicly available and previously published survey data was conducted for SUID events occurring between January 1, 2018 and April 12, 2019 (the date of the first inclined sleeper recall). SUID deaths were categorized as occurring in an AAP-recommended sleep environments or in an inclined sleeper. Exposure Odds Ratios (OR) are reported as the risk of SUID among infants using inclined sleepers relative to an AAP-recommended sleep environment. Results During the study period, 4,900,573 births and 4,363 SUID deaths occurred in the US. Control characteristics were similar between previous night users of an AAP-recommended sleep environment (24%) and inclined sleepers (3.8%). Inclined sleepers were associated with a 5-fold (OR: 5.1; 95% CI: 3.2, 7.9) increased risk of SUID among infants < 12 months compared to infants in an AAP-recommended sleep environment. This risk was greatest among infants ≥ 4 months (RR: 10.4; 95% CI: 5.1, 21.5). Conclusions This novel analysis fills a longstanding gap in risk assessments of inclined infant sleep products. More timely risk analyses may improve the safety of the marketplace.